Optimisasi Pengendalian Persedian Alat Tulis Kantor Menggunakan Metode Min-Max Stock pada BPKP Provinsi Sumatera Utara - Siti Aisyah; Melinda Aprianingsih; Tia Mutiara; Rina Filia Sari; Syuhada Syuhada (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
The use of office stationery (ATK) plays a crucial role in supporting the smooth running of administrative activities within government agencies, particularly within the Financial and Development Supervisory Agency (BPKP). As an agency responsible for supervising and evaluating state financial management, the availability of adequate and timely ATK is a crucial supporting factor in ensuring the efficient and effective operation of BPKP. Unavailability of ATK can hamper administrative processes, while excess stock can lead to budget waste and inefficiency in logistics management. This study aims to implement an inventory control system for ATK use at BPKP using the Min-Max Stock method. This method is used to determine the ideal minimum and maximum limits for ATK inventory, with the aim of minimizing overstock and stockouts. With this approach, agencies can manage ATK procurement more efficiently based on actual needs and existing usage patterns. The results of the study indicate that the application of the Min-Max Stock method provides significant results in inventory management. For the type of ATK in the form of F4 size HVS paper, the minimum and maximum values are set at 12 reams. Meanwhile, for A4-sized HVS paper, the minimum quantity is 72 reams and the maximum is 98 reams. For other types of stationery, such as printer ink, the minimum and maximum quantities are set at 74 and 92 bottles, respectively. For BPKP logo folders, the recommended minimum is 240 sheets and the maximum is 325 sheets. By implementing this method, BPKP can optimally manage stationery inventory, thereby minimizing the risk of stockouts that could disrupt operations and preventing inefficient stockpiling. This approach contributes to more orderly, transparent, and cost-effective logistics governance within the government.